Greetings from Trinidad and Tobago - Hughes, R. (Ace Printery, Trinidad, 2010)
Description on the back of postcard: "Colouful macaw which can be found in Trinidad."
Colour: Coloured (print); Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Macaws--Trinidad and Tobago; Birds--Trinidad and Tobago; Parrots--Trinidad and Tobago